Trends and Health Risk of Trace Metals in Fishes in Liaodong Bay, China, From 2015 to 2020 - Wang, Sujing; Zheng, Na; Sun, Siyu; An, Qirui; Li, Pengyang; Li, Xiaoqian; Li, Zimeng; Zhang, Wenhui (Frontiers in Marine Science, 2022)
Due to their toxicity, non-biodegradability, and biological amplification in the food chain, heavy metal accumulation in humans via the consumption of fishes has become a problem. In this study, we analyzed the concentrations of six trace metals (Cd, Cr, Cu, Ni, Pb, Zn) in 12 marine fish species collected from Liaodong Bay, China, from 2015 to 2020, to understand the pollution status of the bay and evaluate the impact of fish consumption on human health. In addition, 5 fish species with the potential to serve as bioindicators of metal contamination were identified. In general, the average concentrations were Zn > Pb ≈ Cr > Ni ≈ Cu > Cd. There were significant differences in the concentrations in the muscle tissues of fish with different feeding strategies. The total target hazard quotient values of some fish were greater than 1 in 2015, suggesting that people were susceptible to high health risks. The year 2017 had the lowest values, which suggests that metal pollution in Liaodong Bay may have been decreasing at that time. Monitoring of metal concentrations in marine fish from Liaodong Bay warrants more study.